Acantholysis may precede elevation of circulating anti‐desmoglein 3 antibody levels in pemphigus vulgaris presenting with desquamative gingivitis - Hiroyasu Endo; Terry D. Rees; Hideo Niwa; Kayo Kuyama; Maya Oshima; Tae Serizawa; Shigeo Tanaka; Masamichi Komiya; Takanori Ito (Wiley, 2019)
Abstract Pemphigus vulgaris (PV) is an autoimmune, blistering disease that affects the mucosa and skin. The current theory favors the concept that anti‐desmoglein (Dsg) 3 autoimmunity is the only pathogenic event needed to induce acantholysis. However, a few cases of active PV in the oral cavity had no detectable anti‐Dsg 3 antibody. The aim of this study was to evaluate the differences in clinical and laboratory findings, whether or not the anti‐Dsg 3 antibodies were present. This study was based on a retrospective review of 10 PV cases. The evaluation of the circulating autoantibody titers to Dsg 3 was conducted by using enzyme‐linked immunosorbent assay (ELISA). An index value of 20 or more was used as the cutoff for a positive reaction. Only five of the 10 PV cases had a positive Dsg 3 ELISA. There were no differences in clinical, cytological, histopathological, and direct immunofluorescence findings, whether or not the anti‐Dsg 3 antibodies were present. Of the five patients with a negative reaction at the time of diagnosis, the Dsg 3 ELISA became positive in the follow‐up period in three cases. In the remaining two cases, the Dsg 3 ELISA was consistently negative for 18 months. Dsg 3 ELISA was negative early in some PV cases. Therefore, PV acantholysis may precede the elevation of circulating anti‐Dsg 3 antibody levels. The diagnosis of PV should be considered based on comprehensive clinical, histopathological, and immunofluorescent criteria.